Agonist actions of dihydroergotamine at 5-HT(2B) and 5-HT(2C) receptors and their possible relevance to antimigraine efficacy - Schaerlinger, B (2003)
1. The pharmaceutical compound, dihydroergotamine (DHE) is dispensed to prevent and reduce the occurrence of migraine attacks. Although still controversial, the prophylactic effect of this drug is believed to be caused through blockade and/or activation of numerous receptors including serotonin (5-HT) receptors of the 5-HT(2) subtype. 2. To elucidate if 5-HT(2) receptors (5-HT(2)Rs) may be involved in DHE prophylactic effect, we performed investigations aimed to determine the respective pharmacological profile of DHE and of its major metabolite 8′-hydroxy-DHE (8′-OH-DHE) at the 5-HT(2B) and 5-HT(2C)Rs by binding, inositol triphosphate (IP(3)) or cyclic GMP (cGMP) coupling studies in transfected fibroblasts. 3. DHE and 8′-OH-DHE are competitive compounds at 5-HT(2B) and 5-HT(2C)Rs. 8′-OH-DHE interaction at (5-HT(2B)Rs) was best fitted by a biphasic competition curve and displayed the highest affinity with a K(i) of 5 nM. These two compounds acted as agonists for both receptors in respect to cGMP production with pEC(50) of 8.32±0.09 for 8′-OH-DHE at 5-HT(2B) and 7.83±0.06 at 5-HT(2C)Rs. 4. Knowing that the antimigraine prophylactic effect of DHE is only observed after long-term treatment, we chronically exposed the recombinant cells to DHE and 8′-OH-DHE. The number of 5-HT(2B)R-binding sites was always more affected than 5-HT(2C)Rs. At 5-HT(2B)Rs, 8′-OH-DHE was more effective than DHE, with an uncoupling that persisted for more than 40 h for IP(3) or cGMP. By contrast, the 5-HT(2C)R coupling was reversible after either treatment. 5. Chronic exposure to 8′-OH-DHE caused a persistent agonist-mediated desensitisation of 5-HT(2B), but not 5-HT(2C)Rs. This may be of relevance to therapeutic actions of the compound.